A universal synthesis of ultrathin Pd-based nanorings for efficient ethanol electrooxidation. Issue 4 (13th February 2023) - Wang, Yu; Li, Mengfan; Yang, Zhilong; Lai, Wenchuan; Ge, Jingjie; Shao, Minhua; Xiang, Yu; Chen, Xuli; Huang, Hongwen
Abstract : Metallic nanorings (NRs) with an open hollow structure are of particular interest in energy-related catalysis due to their unique features, which include the high utilization of active sites and facile accessibility for reactants. Abstract : Metallic nanorings (NRs) with open hollow structures are of particular interest in energy-related catalysis due to their unique features, which include the high utilization of active sites and facile accessibility for reactants. However, there is still a lack of general methods for synthesizing Pd-based multimetallic NRs with a high catalytic performance. Herein, we develop a template-directed strategy for the synthesis of ultrathin PdM (M = Bi, Sb, Pb, BiPb) NRs with a tunable size. Specifically, ultrathin Pd nanosheets (NSs) are used as a template to steer the deposition of M atoms and the interatomic diffusion between Pd and M, subsequently resulting in the hollow structured NRs. Taking the ethanol oxidation reaction (EOR) as a proof-of-concept application, the PdBi NRs deliver a substantially improved activity relative to the Pd NSs and commercial Pd/C catalysts, simultaneously showing outstanding stability and CO tolerance. Mechanistically, density functional theory (DFT) calculations disclose that the incorporation of Bi reduces the energy barrier of the rate-determining step in the EOR C2 -path, which, together with the high ratio of exposed active sites, endows the PdBi NRs with an excellent EOR activity. We believe that our work can illuminate the general synthesis of multimetallic NRs and the rational design of advanced electrocatalysts.